Wheels in the head : educational philosophies of authority, freedom, and culture from Socrates to human rights - Spring, Joel H. (McGraw-Hill College, 1999)
Autocratic and democratic forms of education. Dissenting traditions in education. The politics of culture. The politics of gender. Education and human rights.